User-oriented ibrary: the experience of updating the space of Tomsk State University Research Library - G. N. Serbina; A. V. Vasiliev (Библиосфера, 2017)
The article considers an approach to the library space organization throw attracting library users to create a joint vision of possible changes. It presents the results of studying readers’ activity experience after a series of reorganization work in reading rooms of Tomsk State University Research Library and results of making the common picture of further changes in the public space.